2022
DOI: 10.1111/mec.16477
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric belowground carbon transfer in a diverse tree community

Abstract: Roots of vascular plants interact with mycorrhizal fungi along withother components of the soil microbiome including nonmycorrhizal fungi, archaea, and bacteria (Högberg et al., 2008). The symbiotic interaction between the fungus and the root relies on transmission of soil-derived nutrients from the fungus to the host tree (Collins Johnson et al., 2010), increasing root absorption of water by the fungal hyphae and mediating the interaction of the root with other microbes in the soil (Aroca et al., 2007;Hestrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 89 publications
(131 reference statements)
0
27
1
Order By: Relevance
“…In the context of our mixed forest, trees A and B can represent EMF and AMF tree hosts, respectively, while mycorrhiza α , β , γ can represent EMF colonizing only EMF tree hosts, AMF colonizing only AMF tree hosts, and EMF colonizing both EMF and AMF tree hosts, respectively. Following studies that demonstrated trees’ resource sharing mediated by mycorrhiza (Klein et al 2016, Rog et al 2020), and specifically in the system studied here (Avital et al 2022, Cahanovitc et al 2022), we assumed in our model that whenever two adjacent trees are colonized by the same mycorrhizal fungi type, a mycorrhizal network is formed, enabling resource sharing between the two trees. We considered the cost to the donor tree and the benefits to the recipients, mediated by the mycorrhizal fungi (distinguishing between intra- and inter-tree-types benefits), as well as the expansion rates of the different mycorrhizal fungi types – the rate at which the hyphae grows and expands from one colonized tree to a neighboring tree, and colonizes it too ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the context of our mixed forest, trees A and B can represent EMF and AMF tree hosts, respectively, while mycorrhiza α , β , γ can represent EMF colonizing only EMF tree hosts, AMF colonizing only AMF tree hosts, and EMF colonizing both EMF and AMF tree hosts, respectively. Following studies that demonstrated trees’ resource sharing mediated by mycorrhiza (Klein et al 2016, Rog et al 2020), and specifically in the system studied here (Avital et al 2022, Cahanovitc et al 2022), we assumed in our model that whenever two adjacent trees are colonized by the same mycorrhizal fungi type, a mycorrhizal network is formed, enabling resource sharing between the two trees. We considered the cost to the donor tree and the benefits to the recipients, mediated by the mycorrhizal fungi (distinguishing between intra- and inter-tree-types benefits), as well as the expansion rates of the different mycorrhizal fungi types – the rate at which the hyphae grows and expands from one colonized tree to a neighboring tree, and colonizes it too ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The computational model we constructed incorporates variability in the ability of different mycorrhizal fungal species to associate with several tree species, as well as for the ability of mycorrhizal fungi to mediate resource sharing between the tree hosts (Avital et al 2022, Cahanovitc et al 2022). We found that generalist mycorrhizal fungi can evolve even when subjected to an expansion rate disadvantage, provided that inter-tree-species cooperation is beneficial enough ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the forest, mycorrhizal fungi, which were missing here, can have large effects too ( Meier et al, 2013 ). Specifically, C. sempervirens hosts a diversity of active arbuscular mycorrhizal species ( Avital et al, 2022 ). While the latter generally help in tree P nutrition, their activity is mostly reduced under drought.…”
Section: Discussionmentioning
confidence: 99%